Electrolyte, electrochemical device and electronic device

By using electrolyte containing lithium difluorophosphate, dinitrile compound and diethyl carbonate in lithium-ion batteries and regulating its content to form a stable interface structure, the performance challenges of lithium-ion batteries at high and low temperatures are solved, and its circulation performance, storage performance and safety are significantly improved.

CN119315104BActive Publication Date: 2025-03-25NINGDE AMPEREX TECHNOLOGY LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411837273.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-25
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

Lithium-ion batteries have challenges in high-temperature cycling performance, high-temperature storage performance, low-temperature discharge performance and safety performance, especially in terms of expansion rate, voltage drop and gas generation.

Method used

An electrolyte including lithium difluorophosphate, dinitrile compound and diethyl carbonate is adopted, and by regulating the mass percentage of dinitrile compound and diethyl carbonate, an interface structure between the electrolyte and the positive electrode sheet is formed under high pressure, improving the acid-base environment at the interface and reducing gas generation during the charge and discharge reaction.

Benefits of technology

It improves the high-temperature cycling performance, high-temperature storage performance, low-temperature discharge performance and safety performance of lithium-ion batteries, reduces the expansion rate and low-temperature voltage drop, and improves the overall performance of the electrochemical device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application provides an electrolyte, an electrochemical device and an electronic device, wherein the electrolyte comprises lithium difluorophosphate, a dinitrile compound and diethyl carbonate, wherein the mass percentage of the dinitrile compound is A%, the mass percentage of diethyl carbonate is B%, 10≤A+B≤24, 0.8≤A≤3 based on the total mass of the electrolyte. The present application adopts an electrolyte comprising lithium difluorophosphate, a dinitrile compound and diethyl carbonate, and regulates the values ​​of A+B and A within the above range, which can improve the high temperature storage performance, high temperature cycle performance, low temperature discharge performance and safety performance of the electrochemical device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical technology, and in particular to an electrolyte, an electrochemical device and an electronic device. Background Art

[0002] With the development of science and technology, people are gradually paying attention to electrochemical devices widely used in portable electronic devices, electric bicycles, electric vehicles and energy storage equipment, and are pursuing higher operating voltage and energy density. During the charging process, gas is easily produced at the internal interface of lithium-ion batteries, which leads to serious expansion of lithium-ion batteries and potential safety hazards. At the same time, the high-temperature storage performance and high-temperature cycle performance of lithium-ion batteries are also facing higher challenges. In addition, the performance of lithium-ion batteries is prone to deterioration at low temperatures and cannot play a normal role. Therefore, the low-temperature performance of lithium-ion batteries has also become a focus of attention. Summary of the invention

[0003] The purpose of the present application is to provide an electrolyte, an electrochemical device and an electronic device to improve the high-temperature cycle performance, high-temperature storage performance, low-temperature discharge performance and safety performance of the electrochemical device.

[0004] In a first aspect, the present application provides an electrolyte, wherein the electrolyte comprises lithium difluorophosphate, a dinitrile compound and diethyl carbonate (DEC), based on the total mass of the electrolyte, the mass percentage of the dinitrile compound is A%, the mass percentage of diethyl carbonate is B%, 10≤A+B≤24, 0.8≤A≤3. The present application adopts an electrolyte comprising lithium difluorophosphate, a dinitrile compound and diethyl carbonate, and the values ​​of A+B and A are regulated within the above ranges. During the charge and discharge process, the chain diethyl carbonate can form an interface structure of the electrolyte and the positive electrode sheet that is stable under high pressure with the dinitrile compound containing two cyano groups, and the difluorophosphate ions can adapt to the diethyl carbonate and the dinitrile compound through chelation to uniformly form a physically and chemically stable interface structure, which can improve the acid-base environment at the interface, reduce the generation of gas during the charge and discharge reaction, improve the expansion rate of the electrochemical device, and reduce the voltage drop of the electrochemical device at low temperature, thereby improving the high-temperature storage performance, high-temperature cycle performance, low-temperature discharge performance and safety performance of the electrochemical device.

[0005] In some embodiments, 12≤A+B≤20. By regulating the value of A+B within the above range, during the charge and discharge process, the chain diethyl carbonate and the dinitrile compound can form a more stable interface structure between the electrolyte and the positive electrode sheet, which can further improve the acid-base environment at the interface, inhibit further oxidative decomposition of the electrolyte during the charge and discharge reaction, reduce the generation of side reactions and the amount of gas generated during the charge and discharge process, thereby further improving the expansion rate of the electrochemical device, and reducing the voltage drop of the electrochemical device at low temperature, and further improving the high temperature storage performance, high temperature cycle performance, low temperature discharge performance and safety performance of the electrochemical device.

[0006] In some embodiments, 15≤A+B≤20. By regulating the value of A+B within the above range, a more stable interface structure between the electrolyte and the positive electrode sheet can be formed, the expansion rate of the electrochemical device can be further improved, the voltage drop of the electrochemical device at low temperature can be reduced, and the high temperature storage performance, high temperature cycle performance, low temperature discharge performance and safety performance of the electrochemical device can be improved.

[0007] In some embodiments, based on the total mass of the electrolyte, the mass percentage of lithium difluorophosphate is E%, 0.05≤E≤2.5. By regulating the value of E within the above range, the chelation effect of difluorophosphate ions with diethyl carbonate and dinitrile compounds can be more fully exerted, and a more physically and chemically stable interface structure can be uniformly formed, and the acid-base environment at the interface can be improved, thereby further reducing the generation of gas during the charge and discharge reaction, improving the expansion rate of the electrochemical device, reducing the voltage drop of the electrochemical device at low temperature, and improving the high-temperature storage performance, high-temperature cycle performance, low-temperature discharge performance and safety performance of the electrochemical device.

[0008] In some embodiments, 1≤A≤2.4. Regulating the mass percentage content A% of the dinitrile compound within the above range helps to form a stable interface structure, optimize the acid-base environment at the interface, inhibit further oxidative decomposition of the electrolyte during the charge and discharge reaction, reduce the generation of side reactions and the amount of gas generated during the charge and discharge process, improve the expansion rate of the electrochemical device, and reduce the voltage drop of the electrochemical device at low temperature, thereby improving the high-temperature storage performance, high-temperature cycle performance, low-temperature discharge performance and safety performance of the electrochemical device.

[0009] In some embodiments, 10≤B≤20. Regulating the mass percentage content B% of diethyl carbonate within the above range helps to form a stable interface structure, optimize the acid-base environment at the interface, inhibit further oxidative decomposition of the electrolyte during the charge and discharge reaction, reduce the generation of side reactions and the amount of gas generated during the charge and discharge process, improve the expansion rate of the electrochemical device, and reduce the voltage drop of the electrochemical device at low temperature, thereby improving the high temperature storage performance, high temperature cycle performance, low temperature discharge performance and safety performance of the electrochemical device.

[0010] In some embodiments, the electrolyte further includes propyl propionate, and the mass percentage of propyl propionate based on the total mass of the electrolyte is D%, 22≤D≤40. By using an electrolyte further including propyl propionate and adjusting the D value within the above range, propyl propionate, dinitrile compounds and diethyl carbonate can form an interface stable structure resistant to high voltage (>4.45V), which can effectively improve the pass rate of the hot box test of the electrochemical device under high temperature (>135°C) conditions, and effectively reduce the generation of gas in the electrochemical device during the heating process, thereby improving the high temperature storage performance, high temperature cycle performance, low temperature discharge performance and safety performance of the electrochemical device.

[0011] In some embodiments, 30≤D≤40. When the D value is adjusted within the above range, propyl propionate, dinitrile compound and diethyl carbonate can form a more high-voltage-resistant interface stable structure, further improve the pass rate of the hot box test of the electrochemical device under high temperature conditions, further reduce the generation of gas in the electrochemical device during the heating process, thereby further improving the high-temperature storage performance, high-temperature cycle performance, low-temperature discharge performance and safety performance of the electrochemical device.

[0012] In some embodiments, the dinitrile compounds include succinonitrile, glutaronitrile, adiponitrile, 1,5-dicyanopentane, 1,6-dicyanohexane, 1,7-dicyanoheptane, 1,8-dicyanooctane, 1,9-dicyanononane, tetramethylsuccinonitrile, 2-methylglutaronitrile, 2,4-dimethylglutaronitrile, 2,2,4,4-tetramethylglutaronitrile, 1,4-dicyanopentane, 2,6-dicyanoheptane, 2,7-dicyanooctane, 2,8-dicyanononane, 1,6-dicyanodecane, 1,2-dicyanobenzene, 1,3-dicyanobenzene, 1,4-dicyanobenzene, 3,5-dioxa-pimelonitrile, 1,4-bis(cyanoethoxy)butane, ethylene glycol di(2-cyano)butane, The invention further comprises at least one of diethylene glycol di(2-cyanoethyl) ether, diethylene glycol di(2-cyanoethyl) ether, triethylene glycol di(2-cyanoethyl) ether, tetraethylene glycol di(2-cyanoethyl) ether, 1,3-bis(2-cyanoethoxy)propane, 1,4-bis(2-cyanoethoxy)butane, ethylene glycol di(4-cyanobutyl) ether, 1,4-dicyano-2-butene, 1,4-dicyano-2-methyl-2-butene, 1,4-dicyano-2-ethyl-2-butene, 1,4-dicyano-2,3-dimethyl-2-butene, 1,4-dicyano-2,3-diethyl-2-butene, 1,6-dicyano-3-hexene or 1,6-dicyano-2-methyl-5-methyl-3-hexene. The electrolyte includes a dinitrile compound within the above range, which can better exert the interaction between lithium difluorophosphate, dinitrile compounds and diethyl carbonate to form a stable interface structure between the electrolyte and the positive electrode plate, which is beneficial to improve the expansion rate of the electrochemical device, reduce the voltage drop of the electrochemical device at low temperature, and improve the high-temperature storage performance, high-temperature cycle performance, low-temperature discharge performance and safety performance of the electrochemical device.

[0013] In some embodiments, the dinitrile compound includes at least one of adiponitrile or ethylene glycol di(2-cyanoethyl)ether. The dinitrile compound within the above range has a certain high voltage window, can be preferentially oxidized over other components, is conducive to forming a more high-voltage resistant interface stable structure, effectively improves the pass rate of the hot box test of the electrochemical device under high temperature conditions, and reduces the generation of gas in the electrochemical device during the heating process, thereby improving the high temperature cycle performance, low temperature discharge performance, safety performance and high temperature storage performance of the electrochemical device.

[0014] In some embodiments, the electrolyte further includes a trinitrile compound, and the mass percentage of the trinitrile compound is C%, 2.6≤A+C≤3.4 based on the total mass of the electrolyte. The electrolyte further includes a trinitrile compound and the total content A+C of the dinitrile compound and the trinitrile compound is regulated within the above range, so that a more compact nitrile structure can be formed between the dinitrile compound with a relatively stable electron cloud distribution and the trinitrile compound with a relatively unstable electron cloud distribution, and the structure can better combine with difluorophosphate ions and diethyl carbonate molecules, inhibit the decomposition of the positive electrode electrolyte interface (CEI) film at high temperature, form a more high-voltage (>4.45V) resistant interface stable structure, and effectively improve the pass rate of the hot box test of the electrochemical device under high temperature conditions, while reducing the generation of gas in the electrochemical device during the heating process, thereby improving the high temperature cycle performance, low temperature discharge performance, safety performance and high temperature storage performance of the electrochemical device.

[0015] In some embodiments, the trinitrile compound includes at least one of 1,3,6-hexane trinitrile or 1,3,5-pentane trinitrile. The use of the above-mentioned trinitrile compounds is conducive to improving the high temperature cycle performance, low temperature discharge performance, safety performance and high temperature storage performance of the electrochemical device.

[0016] A second aspect of the present application provides an electrochemical device, wherein the electrochemical device comprises the electrolyte provided in the first aspect of the present application.

[0017] In some embodiments, the electrochemical device further comprises an isolation membrane, the isolation membrane comprising a base membrane and a porous coating located on at least one surface of the base membrane; on the surface of the porous coating, in a 30 μm×40 μm area, the ratio of the apparent concentration of oxygen element to the apparent concentration of aluminum element is P, 1≤P≤2.5. The present application controls the apparent concentration of oxygen element to the apparent concentration of aluminum element P within the above range, which can reduce the area of ​​contact reaction between the positive and negative electrodes in the hot box test, thereby improving the hot box test pass rate, and at the same time can improve the strength of the isolation membrane itself, enable the permeability of the isolation membrane to be within a suitable range, and can improve the transmission rate of the electrolyte, reduce the blockage and retention of lithium ions on the isolation membrane side, and improve the lithium precipitation phenomenon of the anode, thereby improving the high temperature storage performance, high temperature cycle performance, low temperature discharge performance, safety performance and high temperature floating performance of the electrochemical device.

[0018] In some embodiments, the electrochemical device further comprises a separator, the separator comprising a base film and a porous coating located on at least one surface of the base film; the average wall thickness between adjacent pores in the porous coating is T nm, 25≤T≤450. The present application controls the average wall thickness T nm between adjacent pores in the porous coating within the above range, which can further improve the transmission rate of the electrolyte, reduce the retention of lithium ions in the local area of ​​the separator, reduce the expansion phenomenon of the electrochemical device, and improve the high-temperature storage performance, high-temperature cycle performance, low-temperature discharge performance, safety performance and high-temperature floating performance of the electrochemical device.

[0019] In some embodiments, the electrochemical device further comprises an isolation membrane, the isolation membrane comprising a base membrane and a porous coating located on at least one surface of the base membrane; the compression rate of the base membrane after compression treatment at 70°C and a pressure of 2.5 MPa for 40 minutes is Y%, 25≤Y≤55. The present application controls the compression rate Y% of the base membrane after compression treatment at 70°C and a pressure of 2.5 MPa for 40 minutes within the above range, which can further improve the circulation of the electrolyte in the electrochemical device, reduce the retention of lithium ions in the local area of ​​the isolation membrane, reduce the expansion phenomenon of the electrochemical device, and improve the high-temperature storage performance, high-temperature cycle performance, low-temperature discharge performance, safety performance and high-temperature floating performance of the electrochemical device.

[0020] A third aspect of the present application provides an electronic device, wherein the electronic device includes the electrochemical device provided in the second aspect of the present application.

[0021] The present application provides an electrolyte, an electrochemical device and an electronic device, wherein the electrolyte comprises lithium difluorophosphate, a dinitrile compound and diethyl carbonate, wherein the mass percentage of the dinitrile compound is A%, the mass percentage of the diethyl carbonate is B%, 10≤A+B≤24, 0.8≤A≤3 based on the total mass of the electrolyte. The present application adopts an electrolyte comprising lithium difluorophosphate, a dinitrile compound and diethyl carbonate, and the values ​​of A+B and A are regulated within the above ranges. During the charge and discharge process, the chain diethyl carbonate can form an interface structure of the electrolyte and the positive electrode sheet that is stable under high pressure with the dinitrile compound containing two cyano groups, and the difluorophosphate ions can adapt to the diethyl carbonate and the dinitrile compound through chelation to uniformly form a physically and chemically stable interface structure, and the stable structure can improve the acid-base environment at the interface, reduce the generation of gas during the charge and discharge reaction, improve the expansion rate of the electrochemical device, and reduce the voltage drop of the electrochemical device at low temperature, thereby improving the high-temperature storage performance, high-temperature cycle performance, low-temperature discharge performance and safety performance of the electrochemical device. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.

[0023] In a first aspect, the present application provides an electrolyte, wherein the electrolyte comprises lithium difluorophosphate, a dinitrile compound and diethyl carbonate (DEC). Based on the total mass of the electrolyte, the mass percentage of the dinitrile compound is A%, the mass percentage of diethyl carbonate is B%, 10≤A+B≤24, 0.8≤A≤3. For example, A+B can be 10, 10.5, 11, 11.5, 12, 12.5, 13, 13.5, 14, 14.5, 15, 15.5, 16, 16.5, 17, 17.5, 18, 18.5, 19, 19.5, 20, 20.5, 21, 21.5, 22, 22.5, 23, 23.5, 24, or a range consisting of any two of the values; A can be 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3, or a range consisting of any two of the values. When the value of A is too small, for example, less than 0.8, it is not enough to improve the high temperature storage performance, high temperature cycle performance, low temperature discharge performance and safety performance of the electrochemical device; when the value of A is too large, for example, greater than 3, the interface structure stability of the electrolyte and the positive electrode sheet will deteriorate, the content of other components of the electrolyte will be reduced accordingly, the effect of inhibiting interface gas production will deteriorate, and the effect of reducing the voltage drop at low temperature will deteriorate, which is not conducive to improving the high temperature storage performance, high temperature cycle performance, low temperature discharge performance and safety performance of the electrochemical device. When the value of A+B is too small, for example, less than 10, it is not enough to improve the high temperature storage performance, high temperature cycle performance, low temperature discharge performance and safety performance of the electrochemical device; when the value of A+B is too large, for example, greater than 24, when the content of diethyl carbonate is too much, there will be more diethyl carbonate that is difficult to fully combine with the dinitrile compound, resulting in an increase in by-products at the interface, increased gas production, and poor interface structure stability of the electrolyte and the positive electrode sheet, which is not conducive to improving the high temperature storage performance, high temperature cycle performance, low temperature discharge performance and safety performance of the electrochemical device. The present application adopts an electrolyte including lithium difluorophosphate, a dinitrile compound and diethyl carbonate, and regulates the values ​​of A+B and A within the above range. During the charge and discharge process, the chain diethyl carbonate can form an interface structure between the electrolyte and the positive electrode sheet that is stable under high pressure with the dinitrile compound containing two cyano groups. At the same time, the difluorophosphate ions can adapt to diethyl carbonate and dinitrile compounds through chelation to uniformly form a physically and chemically stable interface structure. The stable structure can improve the acid-base environment at the interface, reduce the generation of gas during the charge and discharge reaction, improve the expansion rate of the electrochemical device, and reduce the voltage drop of the electrochemical device at low temperature, thereby improving the high-temperature storage performance, high-temperature cycle performance, low-temperature discharge performance and safety performance of the electrochemical device. In the present application, the above-mentioned "low temperature" refers to a temperature less than or equal to 0°C.

[0024] In some embodiments, 12≤A+B≤20. For example, A+B can be 12, 12.5, 13, 13.5, 14, 14.5, 15, 15.5, 16, 16.5, 17, 17.5, 18, 18.5, 19, 19.5, 20 or a range consisting of any two of these values. By regulating the value of A+B within the above range, during the charge and discharge process, the chain diethyl carbonate and the dinitrile compound can form a more stable interface structure between the electrolyte and the positive electrode sheet, which can further improve the acid-base environment at the interface, inhibit further oxidative decomposition of the electrolyte during the charge and discharge reaction, reduce the generation of side reactions and the amount of gas generated during the charge and discharge process, further improve the expansion rate of the electrochemical device, and reduce the voltage drop of the electrochemical device at low temperature, thereby further improving the high temperature storage performance, high temperature cycle performance, low temperature discharge performance and safety performance of the electrochemical device.

[0025] In some embodiments, 15≤A+B≤20. For example, A+B can be 15, 15.5, 16, 16.5, 17, 17.5, 18, 18.5, 19, 19.5, 20, or a range consisting of any two of these values. By regulating the value of A+B within the above range, a more stable interface structure between the electrolyte and the positive electrode sheet can be formed, the expansion rate of the electrochemical device can be further improved, the voltage drop of the electrochemical device at low temperature can be reduced, and the high temperature storage performance, high temperature cycle performance, low temperature discharge performance and safety performance of the electrochemical device can be improved.

[0026] In some embodiments, based on the total mass of the electrolyte, the mass percentage of lithium difluorophosphate is E%, 0.05≤E≤2.5. For example, E can be 0.05, 0.06, 0.08, 0.1, 0.12, 0.15, 0.18, 0.2, 0.3, 0.5, 0.6, 0.8, 1.0, 1.2, 1.3, 1.5, 1.6, 1.8, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5 or a range consisting of any two of the values. By regulating the value of E within the above range, the chelation of difluorophosphate ions with diethyl carbonate and dinitrile compounds can be more fully exerted, a more physically and chemically stable interface structure can be uniformly formed, and the acid-base environment at the interface can be improved, thereby further reducing the generation of gas during the charge and discharge reaction, improving the expansion rate of the electrochemical device, reducing the voltage drop of the electrochemical device at low temperature, and improving the high temperature storage performance, high temperature cycle performance, low temperature discharge performance and safety performance of the electrochemical device.

[0027] In some embodiments, 1≤A≤2.4. For example, A can be 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4 or a range consisting of any two of these values. Regulating the mass percentage A% of the dinitrile compound within the above range helps to form a stable interface structure, optimize the acid-base environment at the interface, inhibit further oxidative decomposition of the electrolyte during the charge and discharge reaction, reduce the generation of side reactions and the amount of gas generated during the charge and discharge process, improve the expansion rate of the electrochemical device, and reduce the voltage drop of the electrochemical device at low temperatures, thereby improving the high temperature storage performance, high temperature cycle performance, low temperature discharge performance and safety performance of the electrochemical device.

[0028] In some embodiments, 10≤B≤20. For example, B can be 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 or a range consisting of any two of these values. Regulating the mass percentage B% of diethyl carbonate within the above range helps to form a stable interface structure, optimize the acid-base environment at the interface, inhibit further oxidative decomposition of the electrolyte during the charge and discharge reaction, reduce the generation of side reactions and the amount of gas generated during the charge and discharge process, improve the expansion rate of the electrochemical device, and reduce the voltage drop of the electrochemical device at low temperature, thereby improving the high temperature storage performance, high temperature cycle performance, low temperature discharge performance and safety performance of the electrochemical device.

[0029] In some embodiments, the electrolyte further includes propyl propionate, and the mass percentage of propyl propionate based on the total mass of the electrolyte is D%, 22≤D≤40. For example, D can be 22, 23, 25, 27, 29, 30, 32, 34, 36, 38, 40 or a range consisting of any two of the values. By using an electrolyte that also includes propyl propionate and regulating the D value within the above range, propyl propionate, dinitrile compounds and diethyl carbonate can form an interface stable structure that is resistant to high voltage (>4.45V), which can effectively improve the pass rate of the hot box test of the electrochemical device under high temperature (>135°C), and effectively reduce the generation of gas in the electrochemical device during the heating process, thereby improving the high temperature storage performance, high temperature cycle performance, low temperature discharge performance and safety performance of the electrochemical device.

[0030] In some embodiments, 30≤D≤40. For example, D can be 30, 32, 34, 36, 38, 40 or a range consisting of any two of these values. By regulating the D value within the above range, propyl propionate, dinitrile compounds and diethyl carbonate can form a more high-voltage resistant interface stable structure, further improve the pass rate of the hot box test of the electrochemical device under high temperature conditions, further reduce the generation of gas in the electrochemical device during the heating process, thereby further improving the high-temperature storage performance, high-temperature cycle performance, low-temperature discharge performance and safety performance of the electrochemical device.

[0031] In some embodiments, the dinitrile compounds include succinonitrile, glutaronitrile, adiponitrile, 1,5-dicyanopentane, 1,6-dicyanohexane, 1,7-dicyanoheptane, 1,8-dicyanooctane, 1,9-dicyanononane, tetramethylsuccinonitrile, 2-methylglutaronitrile, 2,4-dimethylglutaronitrile, 2,2,4,4-tetramethylglutaronitrile, 1,4-dicyanopentane, 2,6-dicyanoheptane, 2,7-dicyanooctane, 2,8-dicyanononane, 1,6-dicyanodecane, 1,2-dicyanobenzene, 1,3-dicyanobenzene, 1,4-dicyanobenzene, 3,5-dioxa-pimelonitrile, 1,4-bis(cyanoethoxy)butane, ethylene glycol di(2-cyano)butane, The invention further comprises at least one of diethylene glycol di(2-cyanoethyl) ether, diethylene glycol di(2-cyanoethyl) ether, triethylene glycol di(2-cyanoethyl) ether, tetraethylene glycol di(2-cyanoethyl) ether, 1,3-bis(2-cyanoethoxy)propane, 1,4-bis(2-cyanoethoxy)butane, ethylene glycol di(4-cyanobutyl) ether, 1,4-dicyano-2-butene, 1,4-dicyano-2-methyl-2-butene, 1,4-dicyano-2-ethyl-2-butene, 1,4-dicyano-2,3-dimethyl-2-butene, 1,4-dicyano-2,3-diethyl-2-butene, 1,6-dicyano-3-hexene or 1,6-dicyano-2-methyl-5-methyl-3-hexene. The electrolyte includes a dinitrile compound within the above range, which can better exert the interaction between lithium difluorophosphate, dinitrile compounds and diethyl carbonate to form a stable interface structure between the electrolyte and the positive electrode plate, which is beneficial to improve the expansion rate of the electrochemical device, reduce the voltage drop of the electrochemical device at low temperature, and improve the high-temperature storage performance, high-temperature cycle performance, low-temperature discharge performance and safety performance of the electrochemical device.

[0032] In some embodiments, the dinitrile compound includes at least one of adiponitrile or ethylene glycol di(2-cyanoethyl)ether. The dinitrile compound within the above range has a certain high voltage window, can be preferentially oxidized over other components, is conducive to forming a more high-voltage resistant interface stable structure, effectively improves the pass rate of the hot box test of the electrochemical device under high temperature conditions, and reduces the generation of gas in the electrochemical device during the heating process, thereby improving the high temperature cycle performance, low temperature discharge performance, safety performance and high temperature storage performance of the electrochemical device.

[0033] In some embodiments, the electrolyte further comprises a trinitrile compound, and the mass percentage of the trinitrile compound is C%, based on the total mass of the electrolyte, and 2.6≤A+C≤3.4. For example, A+C can be 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, or a range consisting of any two of the values. The electrolyte also includes a trinitrile compound and the total content A+C of the dinitrile compound and the trinitrile compound is regulated within the above range, so that a tighter nitrile structure can be formed between the dinitrile compound with a relatively stable electron cloud distribution and the trinitrile compound with a relatively unstable electron cloud distribution. The structure can better combine with difluorophosphate ions and diethyl carbonate molecules, inhibit the decomposition of the positive electrode electrolyte interface (CEI) film at high temperature, form an interface stable structure that is more resistant to high voltage (>4.45V), and effectively improve the pass rate of the hot box test of the electrochemical device under high temperature conditions, while reducing the generation of gas in the electrochemical device during the heating process, thereby improving the high temperature cycle performance, low temperature discharge performance, safety performance and high temperature storage performance of the electrochemical device.

[0034] In some embodiments, the trinitrile compound includes at least one of 1,3,6-hexane trinitrile or 1,3,5-pentane trinitrile. The use of the above-mentioned trinitrile compounds is conducive to improving the high temperature cycle performance, low temperature discharge performance, safety performance and high temperature storage performance of the electrochemical device.

[0035] In some embodiments, in addition to lithium difluorophosphate, the electrolyte includes other ionizable lithium salts, including LiPF 6 、LiSbF 6 、LiAsF 6 、LiClO 4 、LiN(C 2 F 5 SO 2 ) 2 CF 3 SO 3 Li、LiC(CF 3 SO 2 ) 3 or LiC 4 BO8 At least one of. The present application does not have any particular limitation on the content of other ionizable lithium salts, as long as the purpose of the present application can be achieved. In some embodiments, based on the total mass of the electrolyte, the mass percentage of other ionizable lithium salts is 8% to 15%, preferably 8% to 12%, and more preferably 8% to 10%. If the content of other ionizable lithium salts is too low, such as less than 8%, the number of mobile lithium ions in the electrolyte may be insufficient, resulting in reduced high-temperature cycle performance of the electrochemical device; if the content of other ionizable lithium salts is too high, such as higher than 15%, the viscosity of the electrolyte may increase, causing an increase in electrolyte impedance, reducing the migration rate of lithium ions, and reducing the high-temperature cycle performance of the electrochemical device. Controlling the content of other ionizable lithium salts within the above range can make the electrolyte have a suitable number of mobile lithium ions, make the viscosity of the electrolyte within a suitable range, improve the migration rate of lithium ions, and enhance the high-temperature cycle performance of the electrochemical device.

[0036] In some embodiments, the electrolyte further includes other additives, including at least one of 1,3-propane sultone (PS), vinyl sulfate (DTD) or vinyl sulfate (VC); further, the other additives also include at least one of 4-methyl ethylene sulfate, 1,4-butane sultone (BS) or 1,3-propene sultone (PST). The present application does not specifically limit the content of other additives, as long as the purpose of the present application can be achieved, for example, based on the total mass of the electrolyte, the mass percentage of other additives is 0.2% to 2.5%.

[0037] In some embodiments, the electrolyte further comprises fluoroether. The present application has no particular limitation on the content of fluoroether, as long as the purpose of the present application can be achieved. For example, based on the total mass of the electrolyte, the total mass percentage of fluoroether is 0.5% to 4.5%.

[0038] In some embodiments, the electrolyte further includes a non-aqueous solvent. The present application has no particular limitation on the non-aqueous solvent, as long as the purpose of the present application can be achieved. For example, the non-aqueous solvent may include but is not limited to at least one of carbonate compounds, carboxylate compounds, ether compounds or other organic solvents.

[0039] The carbonate compound may include but is not limited to at least one of other chain carbonate compounds, cyclic carbonate compounds or fluorinated carbonate compounds other than diethyl carbonate. The other chain carbonate compounds may include but are not limited to at least one of ethyl propionate (EP), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) or ethyl methyl carbonate (EMC). The cyclic carbonate compound may include but is not limited to at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC) or vinyl ethylene carbonate (VEC). The fluorinated carbonate compound may include, but is not limited to, at least one of fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, or trifluoromethylethylene carbonate. The carboxylate compound may include, but is not limited to, at least one of methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, decanolactone, valerolactone, mevalonolactone, caprolactone, or methyl formate. The above-mentioned ether compound may include but is not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate. The present application does not particularly limit the content of the non-aqueous solvent in the electrolyte, as long as the purpose of the present application can be achieved. For example, based on the total mass of the electrolyte, the mass percentage of the non-aqueous solvent is 12% to 81%. For example, the mass percentage of the non-aqueous solvent can be 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 22%, 25%, 30%, 35%, 40%, 45%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 63%, 65%, 70%, 72%, 73%, 75%, 76%, 77%, 78%, 79%, 80%, 81% or a range consisting of any two of the values.

[0040] The second aspect of the present application provides an electrochemical device, wherein the electrochemical device comprises the electrolyte provided in the first aspect of the present application. The electrochemical device provided in the present application has good high temperature storage performance, high temperature cycle performance, low temperature discharge performance and safety performance.

[0041] In some embodiments, the electrochemical device further comprises an isolation membrane, the isolation membrane comprising a base membrane and a porous coating located on at least one surface of the base membrane; on the surface of the porous coating, in a 30 μm×40 μm area, the ratio of the apparent concentration of oxygen element to the apparent concentration of aluminum element is P, 1≤P≤2.5. For example, P can be 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5 or a range consisting of any two of the values. In the present application, the ratio P of the apparent concentration of oxygen element to the apparent concentration of aluminum element can be controlled by regulating the mass ratio of inorganic particles and binder in the porous coating. The present application controls the ratio P of the apparent concentration of oxygen element to the apparent concentration of aluminum element within the above range, which can effectively make the inorganic particles on the isolation membrane have a certain coverage rate on the isolation membrane, thereby reducing the area of ​​contact reaction between the positive and negative electrodes in the hot box test, thereby improving the pass rate of the hot box test, and at the same time improving the strength of the isolation membrane itself, enabling the air permeability of the isolation membrane to be within a suitable range, and improving the transmission rate of the electrolyte, reducing the blockage and retention of lithium ions on the isolation membrane side, and improving the lithium plating phenomenon at the anode, thereby improving the high temperature storage performance, high temperature cycle performance, low temperature discharge performance, safety performance and high temperature floating charge performance of the electrochemical device.

[0042] In some embodiments, the electrochemical device further comprises an isolation membrane, the isolation membrane comprising a base membrane and a porous coating located on at least one surface of the base membrane; the average wall thickness between adjacent pores in the porous coating is T nm, 25≤T≤450. For example, T can be 25, 40, 50, 70, 80, 100, 120, 140, 160, 180, 200, 220, 240, 260, 280, 300, 320, 340, 360, 380, 400, 420, 440, 450 or a range consisting of any two of the values. In the present application, the average wall thickness T nm between adjacent pores in the porous coating can be controlled by adjusting parameters such as the mass ratio of inorganic particles and binder in the porous coating preparation step, the solid content of the porous coating coating solution, the time of immersion in the coagulation solution, the drying temperature and the drying time. Specifically, increasing the mass ratio of inorganic particles and binder in the porous coating increases T; increasing the solid content of the porous coating coating solution decreases T; increasing the time of immersion in the coagulation solution increases T; increasing the drying temperature increases T; increasing the drying time increases T. The present application controls the average wall thickness T nm between adjacent pores in the porous coating within the above range, which can further improve the transmission rate of the electrolyte, reduce the retention of lithium ions in the local area of ​​the separator, reduce the expansion phenomenon of the electrochemical device, and improve the high-temperature storage performance, high-temperature cycle performance, low-temperature discharge performance, safety performance and high-temperature floating performance of the electrochemical device.

[0043] In some embodiments, the electrochemical device further comprises an isolation membrane, the isolation membrane comprising a base membrane and a porous coating located on at least one surface of the base membrane; the compression rate of the base membrane at 70°C under a pressure of 2.5 MPa for 40 minutes is Y%, 25≤Y≤55. For example, Y can be 25, 30, 35, 40, 45, 50, 55 or a range consisting of any two of the values. In the present application, the compression rate Y% of the base membrane at 70°C under a pressure of 2.5 MPa for 40 minutes can be controlled by regulating the molecular weight of the base membrane. The present application controls the compression rate Y% of the base membrane at 70°C under a pressure of 2.5 MPa for 40 minutes within the above range, which can further improve the circulation of the electrolyte in the electrochemical device, reduce the retention of lithium ions in the local area of ​​the isolation membrane, reduce the expansion phenomenon of the electrochemical device, and improve the high temperature storage performance, high temperature cycle performance, low temperature discharge performance, safety performance and high temperature floating performance of the electrochemical device.

[0044] In some embodiments, the base film of the isolation membrane includes at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyethylene terephthalate, polyimide or aramid. For example, polyethylene includes at least one selected from high-density polyethylene, low-density polyethylene or ultra-high molecular weight polyethylene. In some embodiments, the base film of the isolation membrane includes at least one of polyethylene or polypropylene, which has a good effect on preventing short circuits and can improve the safety performance of electrochemical devices through the shutdown effect. The present application does not have any special restrictions on the molecular weight of the base film, as long as the purpose of the present application can be achieved. In some embodiments, the molecular weight of the base film is 0.4×10 6 to 1.4×10 6 For example, the molecular weight of the base film can be 0.4×10 6 , 0.5×10 6 , 0.6×10 6 , 0.7×10 6 , 0.8×10 6 , 0.9×10 6 , 1.0×10 6 , 1.1×10 6 , 1.2×10 6 , 1.3×10 6 , 1.4×10 6 Or a range consisting of any two values.

[0045] In some embodiments, the porous coating comprises a first inorganic particle and a binder, the first inorganic particle being selected from alumina (Al 2 O 3 ), boehmite or aluminum hydroxide. The present application has no particular restrictions on the binder, as long as the purpose of the present application can be achieved. For example, the binder is selected from at least one of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polyvinyl ether, polytetrafluoroethylene or polyhexafluoropropylene. The isolation membrane with a porous coating of the present application can improve the heat resistance, oxidation resistance and electrolyte wetting performance of the isolation membrane, and enhance the adhesion between the isolation membrane and the pole piece. In some embodiments, the mass ratio of the first inorganic particles to the binder is 60:40 to 98:2; for example, the mass ratio of the first inorganic particles to the binder can be 60:40, 65:35, 70:30, 75:25, 80:20, 85:15, 90:10, 95:5, 98:2 or a range consisting of any two of the values. In some embodiments, the pore diameter of the separator porous coating layer is 0.01 μm to 1 μm.

[0046] In some embodiments, the preparation step of the porous coating of the isolation membrane includes: mixing the first inorganic particles and the binder in a mass ratio, then adding the first solvent and stirring evenly to obtain a porous coating coating liquid with a solid content of 5-55wt%, applying it on the surface of the isolation membrane, immersing it in the coagulation liquid for 15s to 100s, and then drying it at a temperature of 20°C to 100°C for 0.5h to 6h to obtain an isolation membrane with a porous coating. The present application has no special restrictions on the first solvent, as long as the purpose of the present application can be achieved, for example, the first solvent is N-methylpyrrolidone. The present application has no special restrictions on the coagulation liquid, as long as the purpose of the present application can be achieved, for example, the coagulation liquid includes a second solvent and a third solvent, and the mass percentage of the second solvent is 30% to 50% based on the total mass of the coagulation liquid. For example, the second solvent is N-methylpyrrolidone and the third solvent is deionized water.

[0047] In some embodiments, the isolation film further comprises an inorganic heat-resistant coating, which is located on at least one surface of the base film. In some embodiments, the inorganic heat-resistant coating is located between the base film and the porous coating. In some embodiments, the inorganic heat-resistant coating comprises a second inorganic particle and a binder, and the second inorganic particle is selected from aluminum oxide (Al 2 O 3 ), silicon oxide (SiO 2 )、MgO、TiO 2 )、HfO 2 )、Tin Oxide(SnO 2 ), cerium dioxide (CeO 2 )、nickel oxide (NiO), zinc oxide (ZnO), calcium oxide (CaO), zirconium oxide (ZrO 2 ), yttrium oxide (Y 2 O 3 ), at least one of silicon carbide (SiC), boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application has no particular limitation on the binder, as long as the purpose of the present application can be achieved. For example, the binder can be at least one of the above binders. The present application has no particular limitation on the mass ratio of the second inorganic particles to the binder, as long as the purpose of the present application can be achieved. For example, the mass ratio of the second inorganic particles to the binder is 80 to 90:10 to 20.

[0048] In some embodiments, the isolation film includes a base film, a first inorganic heat-resistant coating and an organic coating located on one surface of the base film, a second inorganic heat-resistant coating and a porous coating located on the other surface of the base film, the first inorganic heat-resistant coating is located between the base film and the organic coating, and the second inorganic heat-resistant coating is located between the base film and the porous coating. In some embodiments, the organic coating includes a high-temperature resistant resin, and the high-temperature resistant resin includes at least one of a high-melting-point crystalline polymer or a high-temperature resistant amorphous polymer. The high-melting-point crystalline polymer includes at least one of polypropylene, poly-4-methylpentene, polytetrafluoroethylene or polyvinylidene fluoride, and the high-temperature resistant amorphous polymer includes a cycloolefin copolymer. Based on the mass of the base film, the mass percentage Z% of the high-temperature resistant resin is 2.5% to 9%. For example, the mass percentage Z% of the high-temperature resistant resin can be 2.5%, 3%, 5%, 7%, 8%, 9% or a range composed of any two of the values. When an isolation film including the organic coating of the above-mentioned high-temperature resistant resin is used and the mass percentage of the high-temperature resistant resin is regulated within the above range, it is beneficial to improve the melting temperature and strength of the isolation film and to improve the high-temperature performance of the electrochemical device.

[0049] In some embodiments, the isolation film may have a thickness of 3 μm to 480 μm.

[0050] In some embodiments, the electrochemical device further comprises a positive electrode sheet and a negative electrode sheet, and the separator is located between the positive electrode sheet and the negative electrode sheet.

[0051] In some embodiments, the positive electrode sheet includes a positive current collector and a positive active material layer disposed on at least one surface of the positive current collector. The above-mentioned "positive active material layer disposed on at least one surface of the positive current collector" means that the positive active material layer can be disposed on one surface of the positive current collector along its own thickness direction, or it can be disposed on two surfaces of the positive current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of ​​the surface of the positive current collector, or it can be a partial area of ​​the surface of the positive current collector. This application is not particularly limited, as long as the purpose of this application can be achieved. This application has no special restrictions on the positive current collector, as long as the purpose of this application can be achieved, for example, it can include aluminum foil, aluminum alloy foil or composite current collector (such as aluminum-carbon composite current collector). This application has no special restrictions on the thickness of the positive current collector and the positive active material layer, as long as the purpose of this application can be achieved. For example, the thickness of the positive current collector can be 1μm to 200μm, and the thickness of the positive active material layer can be 10μm to 500μm. It should be understood that these are only exemplary, and other suitable thicknesses can also be used.

[0052] In some embodiments, the positive electrode active material layer includes a positive electrode active material. The present application has no particular limitation on the positive electrode active material, as long as the purpose of the present application can be achieved. For example, the positive electrode active material may include but is not limited to lithium cobalt oxide (LiCoO 2 ), lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium nickel cobalt manganese oxide (for example, NCM811, NCM622, NCM523, NCM111), lithium nickel cobalt aluminum oxide or lithium nickel manganese oxide. In some embodiments, the above-mentioned positive electrode active materials can be doped and / or coated.

[0053] In some embodiments, the positive electrode active material layer further includes a positive electrode binder and a positive electrode conductor. The present application does not particularly limit the types of the positive electrode binder and the positive electrode conductor, as long as the purpose of the present application can be achieved. For example, the positive electrode binder may include but is not limited to polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, styrene-acrylate copolymer, styrene-butadiene copolymer, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinyl acetate, polyvinylpyrrolidone, polyvinyl ether, polytetrafluoroethylene or polyhexafluoropropylene. At least one. For example, the positive electrode conductor may include but is not limited to at least one of conductive carbon black (Super P), graphene, carbon nanotubes or carbon fibers. Conductive carbon black may include but is not limited to at least one of acetylene black or Ketjen black. Carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. Carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nanocarbon fibers. The present application has no particular restriction on the mass ratio of the positive electrode active material, the positive electrode conductive agent, and the positive electrode binder in the positive electrode active material layer. Those skilled in the art can select the ratio according to actual needs as long as the purpose of the present application can be achieved.

[0054] In some embodiments, the surface of the positive electrode active material layer further includes a covering layer, the covering layer includes lithium phosphate and lithium niobate, the mass ratio of which is 1:3 to 1:1, and the thickness of the covering layer is 1 μm to 1.8 μm.

[0055] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector. The above-mentioned "negative electrode active material layer is disposed on at least one surface of the negative electrode current collector" means that the negative electrode active material layer can be disposed on one surface of the negative electrode current collector along its own thickness direction, or it can be disposed on two surfaces of the negative electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of ​​the surface of the negative electrode current collector, or it can be a partial area of ​​the surface of the negative electrode current collector. This application is not particularly limited, as long as the purpose of this application can be achieved. This application has no special restrictions on the negative electrode current collector, as long as the purpose of this application can be achieved, for example, it can include at least one of copper foil, nickel foil or carbon-based current collector. This application has no special restrictions on the thickness of the negative electrode current collector, as long as the purpose of this application can be achieved, for example, the thickness of the negative electrode current collector can be 1μm to 200μm. This application has no special restrictions on the thickness of the negative electrode active material layer, as long as the purpose of this application can be achieved, for example, the thickness of the negative electrode active material layer can be 10μm to 500μm. It should be understood that these are exemplary only and other suitable thicknesses may be used.

[0056] In some embodiments, the negative electrode active material layer includes a negative electrode active material. The present application has no particular restrictions on the negative electrode active material, as long as the purpose of the present application can be achieved. For example, the negative electrode active material includes but is not limited to at least one of natural graphite, artificial graphite or silicon-based materials. In some embodiments, the silicon-based material includes at least one of silicon, silicon-oxygen compounds, silicon-carbon compounds or silicon alloys.

[0057] In some embodiments, the negative electrode active material layer may also include a negative electrode conductor and / or a negative electrode binder. The present application does not particularly limit the types of the negative electrode conductor and the negative electrode binder, as long as the purpose of the present application can be achieved. For example, the negative electrode conductor may include but is not limited to at least one of conductive carbon black (Super P), graphene, carbon nanotubes or carbon fibers. Conductive carbon black may include but is not limited to at least one of acetylene black or Ketjen black. Carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. Carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nano-carbon fibers. For example, the negative electrode binder may include but is not limited to at least one of carboxymethyl cellulose (CMC), polyacrylic acid, polyacrylic acid salt, polyacrylic acid ester, polyvinyl pyrrolidone, polyimide, polysiloxane or styrene-butadiene rubber. It should be understood that the above materials are only exemplary, and the negative electrode active material layer may use any other suitable materials. The present application does not particularly limit the mass ratio of the negative electrode active material, the negative electrode conductor and the negative electrode binder in the negative electrode active material layer. Those skilled in the art may select according to actual needs, as long as the purpose of the present application can be achieved. In some embodiments, the mass ratio of the negative electrode active material, the negative electrode conductor and the negative electrode binder in the negative electrode active material layer can be (80~99):(0.5~10):(0.5~10). It should be understood that this is only exemplary and is not intended to limit the present application.

[0058] The electrochemical device also includes a housing for accommodating a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte, as well as other components known in the field of electrochemical devices, and this application does not limit the above-mentioned other components. This application does not particularly limit the housing, and it can be a housing known in the art, as long as the purpose of this application can be achieved. For example, the housing can be a hard shell housing or a flexible shell. The material of the hard shell housing can be metal, and this application does not limit the type of metal, and a metal hard shell housing known in the art can be used, as long as the purpose of this application can be achieved. The flexible housing can be a metal plastic film, such as an aluminum plastic film, a steel plastic film, etc.

[0059] In some embodiments, the electrochemical device is a lithium ion battery, but the application is not limited thereto.

[0060] The preparation process of the electrochemical device of the present application is well known to those skilled in the art, and the present application has no particular limitations. For example, the preparation process of the electrochemical device may include but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain an electrode assembly with a wound structure, placing the electrode assembly in a shell, injecting the electrolyte into the shell and sealing it to obtain an electrochemical device. Alternatively, stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and then fixing the four corners of the entire stacked structure with tape to obtain an electrode assembly with a stacked structure, placing the electrode assembly in a shell, injecting the electrolyte into the shell and sealing it to obtain an electrochemical device. In addition, overcurrent protection elements, guide plates, etc. may also be placed in the shell as needed to prevent pressure rise and overcharge and discharge inside the electrochemical device.

[0061] In some embodiments, taking lithium-ion batteries as an example, the positive electrode sheet, the separator, and the negative electrode sheet are wound or stacked in sequence to form an electrode assembly, which is then placed in a shell such as an aluminum-plastic film, injected with electrolyte, formed, and packaged to make a lithium-ion battery.

[0062] The third aspect of the present application provides an electronic device, wherein the electronic device includes the electrochemical device provided in the second aspect of the present application. Thus, the electronic device provided by the present application has good performance. The present application does not particularly limit the type of electronic device, and it can be used for any electronic device known in the prior art. In some embodiments, the electronic device may include but is not limited to a laptop computer, a pen-input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, a liquid crystal television, a portable cleaner, a portable CD player, a mini disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium ion capacitor, etc.

[0063] Example

[0064] Hereinafter, the embodiments of the present application are described in more detail by way of examples and comparative examples, wherein a lithium ion battery is used as an example, but the electrochemical device of the present application is not limited to a lithium ion battery. Various tests and evaluations are performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.

[0065] Test methods and equipment:

[0066] Low temperature voltage drop test:

[0067] At 25°C, the lithium-ion battery was charged to 4.5V at 1C constant current, then charged to 0.05C at constant voltage, and then discharged to 3.2V at 1.5C constant current, and left to stand for 5 minutes, and then the voltage was tested. After being stored at -20°C for 30 hours, the voltage was retested. Low temperature voltage drop (V) = voltage before storage - voltage after storage.

[0068] Thickness expansion rate test:

[0069] At 65°C, the lithium-ion battery is charged to 4.5V at a constant current of 1C, then charged to a current of 0.05C at a constant voltage, and then discharged to 3V at a constant current of 1C. This is the first cycle. The lithium-ion battery is cycled 20 times under the above conditions. The thickness of the lithium-ion battery before and after the cycle is measured at room temperature using a height gauge. Calculate the thickness expansion rate: Thickness expansion rate (%) = (thickness after cycle - thickness before cycle) / thickness before cycle × 100%.

[0070] 60℃ Cycle Performance Test:

[0071] In a 60°C environment, the lithium-ion battery is charged and discharged for the first time: constant current charging is performed at a charging current of 2C to a full charge voltage of 4.5V, then constant voltage charging is performed at a maximum voltage of 4.5V until the current is 0.02C, and then constant current discharge is performed at a discharge current of 0.5C until the final voltage is 3.0V, and the discharge capacity of the first cycle is recorded; then the above steps are repeated for 600 charge and discharge cycles, and the discharge capacity of the 600th cycle is recorded. 60°C cycle capacity retention rate (%) = (discharge capacity of the 600th cycle / discharge capacity of the first cycle) × 100%.

[0072] High temperature floating charge cycle capacity retention test:

[0073] Place the lithium-ion battery in a 25℃ constant temperature box and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. Charge with a 1C constant current to a voltage of 4.5V, charge with a constant voltage to a current of 0.05C, and then discharge with a 1C constant current to a voltage of 3V. Record the discharge capacity as the initial discharge capacity of the lithium-ion battery. Then charge with a 0.5C constant current to a voltage of 4.5V, and charge with a constant voltage to a current of 0.05C. Transfer the lithium-ion battery to a 45℃ constant temperature box, and then charge with a 4.5V constant voltage for 40 days. After 40 days, transfer the lithium-ion battery to a 25℃ constant temperature box, let it stand for 60 minutes, and discharge with a 1C constant current to a voltage of 2.8V. Then charge with a 1C constant current to a voltage of 4.5V, charge with a constant voltage to a current of 0.05C, and then discharge with a 1C constant current to 3V. Record the discharge capacity as the recoverable capacity of the lithium-ion battery. High temperature floating charge cycle capacity retention rate (%) = (initial discharge capacity - recoverable capacity) / initial discharge capacity × 100%.

[0074] Hot box test:

[0075] Charge the lithium-ion battery at room temperature at a constant current of 0.5C rate to a full charge voltage of 4.2V, and continue to charge at a constant voltage of 4.2V to a cutoff current of 0.05C, so that the lithium-ion battery is in a fully charged state, check the appearance, and ensure that the lithium-ion battery is in a normal usable state. Put the fully charged lithium-ion battery into an oven and heat it at a rate of 5°C / min until it reaches the specified hot box test temperature of 140°C. Keep the temperature constant for one hour, and observe the state of the lithium-ion battery during this process. Twenty lithium-ion batteries of each embodiment or comparative example are tested as parallel samples. Judgment criteria: The lithium-ion battery does not catch fire or explode. Hot box test pass rate (%) = number of hot box test passes / total number × 100%.

[0076] Electrolyte component test:

[0077] The lithium-ion battery was disassembled to obtain the electrolyte, and the electrolyte components were tested using a gas chromatography-mass spectrometer (GC-MS, model: AgilentGC7890A). The mass percentages of the electrolyte components, lithium difluorophosphate, dinitrile compounds, diethyl carbonate, propyl propionate, and trinitrile compounds, were calculated using the external standard method.

[0078] Tests of apparent concentration of oxygen and aluminum:

[0079] The isolation membrane was obtained by disassembling the lithium-ion battery, and the porous coating surface of the isolation membrane was measured by an energy dispersive spectrometer (EDS, model: EDAX Octane SDD). The apparent concentration of oxygen and the apparent concentration of aluminum in the 30μm×40μm area were tested. The ratio of the apparent concentration of oxygen to the apparent concentration of aluminum was P = apparent concentration of oxygen / apparent concentration of aluminum.

[0080] Test for average wall thickness between adjacent pores in porous coatings:

[0081] The separator was obtained by disassembling the lithium-ion battery. A scanning electron microscope (SEM) was used to test a 5μm×5μm area of ​​the porous coating of the separator. The wall thickness between every two adjacent holes in 25 evenly distributed adjacent holes was measured, and the average wall thickness T nm was calculated.

[0082] The compression rate test of the base film at 70°C and a pressure of 2.5 MPa for 40 minutes:

[0083] The lithium-ion battery was disassembled to obtain the isolation membrane, the coating on the surface of the isolation membrane was scraped off, and the initial thickness H1 of the base membrane was measured. The base membrane was compressed at 70°C and a pressure of 2.5 MPa for 40 minutes. The thickness of the base membrane after the treatment was measured to be H2, and the compression rate Y%=[(H1-H2) / H1]×100%.

[0084] Example 1-1

[0085] <Preparation of positive electrode sheet>

[0086] The positive electrode active material is lithium cobalt oxide (LiCoO 2 ), conductive carbon black (Super P), and binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 97:1:2, N-methylpyrrolidone (NMP) is added, and the mixture is stirred evenly under the action of a vacuum mixer to obtain a positive electrode slurry with a solid content of 65wt%. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 12μm, and the aluminum foil is dried at 120℃ for 1h to obtain a positive electrode sheet coated with a positive electrode active material layer with a thickness of 80μm on one side. Repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet coated with a positive electrode active material layer on both sides. Then, after cold pressing, cutting, and slitting, it is dried under vacuum conditions at 120℃ for 1h to obtain a positive electrode sheet with a specification of 74mm (width) × 867mm (length), and a positive electrode current collector empty foil area is left at one end of the length direction.

[0087] Alumina (Dv99 is 0.7 μm) and binder PVDF are mixed in a mass ratio of 80:20, NMP is added, and the mixture is stirred evenly under the action of a vacuum mixer to obtain a positive inorganic coating slurry with a solid content of 30 wt%. The positive inorganic coating slurry is evenly coated on one of the surfaces of the aluminum foil in the positive current collector empty foil area at the tail of the above-mentioned positive electrode sheet (this surface is defined as the a surface, and the other surface of the positive current collector is defined as the b surface), and dried at 120°C for 1 hour to obtain a positive electrode sheet with a positive inorganic coating on the a surface of the positive current collector, and the length of the positive inorganic coating is 95 mm and the thickness is 2.5 μm.

[0088] <Preparation of negative electrode sheet>

[0089] The negative electrode active material artificial graphite, conductive agent conductive carbon black, binder styrene butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) were mixed in a weight ratio of 96.5:1.5:1:1, deionized water was added, and the mixture was stirred evenly under the action of a vacuum mixer to obtain a negative electrode slurry, wherein the solid content of the negative electrode slurry was 75wt%. The negative electrode slurry was evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 12μm, and dried at 120°C to obtain a negative electrode sheet coated with a negative electrode active material layer with a thickness of 90μm on one side, and the above steps were repeated on the other surface of the negative electrode current collector copper foil to obtain a negative electrode sheet coated with a negative electrode active material layer on both sides, and then after cold pressing, cutting, and slitting, a negative electrode sheet with a specification of 76mm (width)×874mm (length) was obtained.

[0090] <Preparation of Electrolyte>

[0091] In an argon atmosphere glove box with a water content of less than 10 ppm, ethylene carbonate (EC) was first heated at a high temperature of 60°C to convert it into a liquid state, and then a non-aqueous solvent was prepared according to a mass ratio of ethylene carbonate (EC): ethyl methyl carbonate (EMC): propylene carbonate (PC) = 1:2:1, and then diethyl carbonate (DEC), propyl propionate, lithium hexafluorophosphate, lithium difluorophosphate, and dinitrile compound ethylene glycol di(2-cyanoethyl) ether were added and mixed uniformly to obtain an electrolyte. Among them, based on the total mass of the electrolyte, the mass percentage of lithium hexafluorophosphate is 12.50%, the mass percentage of lithium difluorophosphate is E% is 0.50%, the mass percentage of dinitrile compound is A% is 0.80%, the mass percentage of propyl propionate is D% is 30.00%, the mass percentage of diethyl carbonate is B% is 15.00%, and the balance is non-aqueous solvent.

[0092] <Preparation of Separator Film>

[0093] The thickness is 10 μm and the molecular weight is 1.3×10 6 A polyethylene (PE) microporous membrane (provided by Shanghai Enjie Company) is used as the base membrane of the isolation membrane, one surface of the base membrane is defined as the c-side, and the other surface is defined as the d-side.

[0094] Preparation of isolation film c surface coating:

[0095] Inorganic boehmite particles with a Dv50 of 1.1µm and polyacrylate are mixed in a mass ratio of 85:15 and dissolved in deionized water to form an inorganic heat-resistant coating slurry with a solid content of 47wt%. The resulting inorganic heat-resistant coating slurry is then evenly coated on one surface of a PE base film using a micro-concave coating method, and dried in an oven at 120°C to obtain an isolation film with a c-side coated with an inorganic heat-resistant coating with a thickness of 1.8μm.

[0096] Add the first polymer polypropylene (PP) to the stirrer and stir evenly; add sodium carboxymethyl cellulose to the stirrer and stir evenly; add dimethyl siloxane, a wetting agent, to the stirrer, then add deionized water and stir, adjust the viscosity of the slurry to 45mPa•s and the solid content to 6wt%, and obtain an organic coating slurry. The organic coating slurry is evenly coated on the surface of the inorganic heat-resistant coating on the c side of the isolation membrane, and after drying in an oven at 120°C, an isolation membrane with a c side coated with an organic coating with a thickness of 3μm and an inorganic heat-resistant coating with a thickness of 1.8μm is obtained. Among them, the mass ratio of the first polymer, sodium carboxymethyl cellulose, and dimethyl siloxane is 95:0.5:4.5.

[0097] Preparation of isolation film top coating:

[0098] Inorganic boehmite particles with a Dv50 of 1.1µm and polyacrylate are mixed in a mass ratio of 85:15 and dissolved in deionized water to form an inorganic heat-resistant coating slurry with a solid content of 47wt%. The resulting inorganic heat-resistant coating slurry is then evenly coated on the other surface of the PE base film using a micro-concave coating method, and dried in an oven at 120°C to obtain an isolation film with the d side coated with an inorganic heat-resistant coating with a thickness of 1.8μm.

[0099] The inorganic particle boehmite and the binder polyvinylidene fluoride are mixed in a mass ratio of M1:M2=85:15, and then N-methylpyrrolidone (the first solvent) is added and stirred evenly to obtain a porous coating liquid with a solid content of 8wt%; the porous coating liquid is coated on the surface of the inorganic heat-resistant coating on the d side of the isolation membrane by a dip coating method to form a wet film; the isolation membrane with the wet film is immersed in a solidifying liquid containing deionized water (the third solvent) and N-methylpyrrolidone (the second solvent); The phase inversion is carried out in the coagulation liquid, and after being immersed in the coagulation liquid for 30 seconds, it is placed in an oven and dried at 60°C for 2 hours to obtain an isolation membrane with a porous coating with a thickness of 3 μm and an inorganic heat-resistant coating with a thickness of 1.8 μm on the d side, and an organic coating with a thickness of 3 μm and an inorganic heat-resistant coating with a thickness of 1.8 μm on the c side, wherein the mass percentage of N-methylpyrrolidone (the second solvent) in the coagulation liquid is 38%, and the balance is the third solvent, and the temperatures of the porous coating coating liquid and the coagulation liquid are both 25°C.

[0100] <Preparation of lithium-ion batteries>

[0101] The positive electrode sheet, separator, and negative electrode sheet prepared above are stacked in order, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, wherein the a surface of the positive electrode sheet faces the d surface of the separator, and the electrode assembly is wound to obtain the electrode assembly. After welding the pole ears, the electrode assembly is placed in an outer packaging aluminum-plastic film, and after dehydration at 80°C, the above-mentioned electrolyte is injected, and after vacuum packaging, standing, forming (the upper limit voltage of formation is 4.5V, the formation temperature is 70°C, and the formation standing time is 2 hours), shaping, capacity testing and other processes, a lithium-ion battery is obtained.

[0102] Example 1-2 to Example 1-30

[0103] Except that the mass percentage A of the dinitrile compound, the mass percentage B of diethyl carbonate, the type of the dinitrile compound, the mass percentage E of lithium difluorophosphate are adjusted as shown in Table 1 in <Preparation of Electrolyte>, the mass percentage of the non-aqueous solvent is changed accordingly, the mass percentage of propyl propionate remains unchanged, and the mass percentage of lithium hexafluorophosphate remains unchanged, the rest is the same as Example 1-1.

[0104] Example 2-1 to Example 2-13

[0105] The preparation method is the same as that of Example 1-2, except that propyl propionate and / or the trinitrile compound 1,3,6-hexanetrinitrile are added as shown in Table 2 in <Preparation of Electrolyte>, and the mass percentage content D%, the mass percentage content C% of the trinitrile compound are adjusted as shown in Table 2, the mass percentage content of the non-aqueous solvent changes accordingly, the mass percentage content of the dinitrile compound remains unchanged, the mass percentage content of diethyl carbonate remains unchanged, the mass percentage content of lithium hexafluorophosphate remains unchanged, and the mass percentage content of lithium difluorophosphate remains unchanged.

[0106] Example 3-1 to Example 3-12

[0107] Except for adjusting the corresponding preparation parameters in <Preparation of Isolation Film> as shown in Table 3, so that the ratio P of the apparent concentration of oxygen element to the apparent concentration of aluminum element, the average wall thickness T nm between adjacent pores in the porous coating, and the compression rate Y% of the base film compressed at 70°C under a pressure of 2.5 MPa for 40 minutes are as shown in Table 3, the rest are the same as Example 1-2.

[0108] Comparative Example 1-1 to Comparative Example 1-6

[0109] Except that the mass percentage of the dinitrile compound A%, the mass percentage of diethyl carbonate B%, and the mass percentage of lithium difluorophosphate E% are adjusted according to Table 1 in <Preparation of Electrolyte>, the mass percentage of the non-aqueous solvent changes accordingly, the mass percentage of propyl propionate remains unchanged, and the mass percentage of lithium hexafluorophosphate remains unchanged, the rest is the same as Example 1-1.

[0110] Table 1

[0111]

[0112] Note: “ / ” in Table 1 means there is no corresponding preparation parameter.

[0113] Table 2

[0114]

[0115] Note: “ / ” in Table 2 indicates no corresponding preparation parameters.

[0116] Table 3

[0117]

[0118] It can be seen from Examples 1-1 to 1-30 and Comparative Examples 1-1 to 1-6 that when the electrolyte includes lithium difluorophosphate, a dinitrile compound and diethyl carbonate, and the value of the dinitrile compound content A and the value of the total content A+B of the dinitrile compound and diethyl carbonate are regulated within the scope of the present application, the lithium ion battery has a lower thickness expansion rate, a lower low-temperature voltage drop, a higher high-temperature cycle capacity retention rate and a higher hot box test pass rate, indicating that the lithium ion battery has good safety performance, low-temperature discharge performance, high-temperature cycle performance and high-temperature storage performance.

[0119] The value of the lithium difluorophosphate content E usually affects the safety performance, low temperature discharge performance, high temperature cycle performance and high temperature storage performance of the lithium ion battery. It can be seen from Examples 1-2, 1-23 to 1-30 that when the value of E is adjusted within the range of the present application, the lithium ion battery has a lower thickness expansion rate, a lower low temperature voltage drop, a higher high temperature cycle capacity retention rate and a higher hot box test pass rate, indicating that the lithium ion battery has good safety performance, low temperature discharge performance, high temperature cycle performance and high temperature storage performance.

[0120] The value of the dinitrile compound content A and / or the diethyl carbonate content B usually affects the safety performance, low temperature discharge performance, high temperature cycle performance and high temperature storage performance of the lithium ion battery. It can be seen from Examples 1-1 to 1-20 that when the values ​​of A and / or B are regulated within the scope of the present application, the lithium ion battery has a lower thickness expansion rate, a lower low temperature voltage drop, a higher high temperature cycle capacity retention rate and a higher hot box test pass rate, indicating that the lithium ion battery has good safety performance, low temperature discharge performance, high temperature cycle performance and high temperature storage performance.

[0121] The type of dinitrile compound usually affects the safety performance, low temperature discharge performance, high temperature cycle performance and high temperature storage performance of lithium ion batteries. It can be seen from Examples 1-2, 1-21 and 1-22 that lithium ion batteries using dinitrile compounds of the type within the scope of this application have lower thickness expansion rate, lower low temperature voltage drop, higher high temperature cycle capacity retention rate and higher hot box test pass rate, indicating that lithium ion batteries have better safety performance, low temperature discharge performance, high temperature cycle performance and high temperature storage performance.

[0122] The value of the content D of propyl propionate usually affects the safety performance, low temperature discharge performance, high temperature cycle performance and high temperature storage performance of the lithium ion battery. It can be seen from Examples 1-2 and 2-1 to 2-7 that by using an electrolyte that also includes propyl propionate and regulating the value of the propyl propionate content D within the scope of the present application, the lithium ion battery has a lower thickness expansion rate, a lower low temperature voltage drop, a higher high temperature cycle capacity retention rate and a higher hot box test pass rate, indicating that the lithium ion battery has better safety performance, low temperature discharge performance, high temperature cycle performance and high temperature storage performance.

[0123] The value of the total content A+C of dinitrile compounds and trinitrile compounds usually affects the safety performance, low temperature discharge performance, high temperature cycle performance and high temperature storage performance of lithium ion batteries. It can be seen from Examples 2-1, 2-8 to 2-13 that by using an electrolyte that also includes trinitrile compounds and regulating the value of the total content A+C of dinitrile compounds and trinitrile compounds within the scope of this application, the lithium ion battery has a lower thickness expansion rate, a lower low temperature voltage drop, a higher high temperature cycle capacity retention rate and a higher hot box test pass rate, indicating that the lithium ion battery has better safety performance, low temperature discharge performance, high temperature cycle performance and high temperature storage performance.

[0124] The value of the ratio P of the apparent concentration of oxygen elements on the surface of the porous coating of the isolation membrane to the apparent concentration of aluminum elements, the value of the average wall thickness T between adjacent pores in the porous coating of the isolation membrane, and the value of the compression ratio Y of the isolation membrane base film at 70°C under a pressure of 2.5MPa for 40 minutes usually affect the safety performance, low-temperature discharge performance, high-temperature cycle performance, high-temperature storage performance and high-temperature floating performance of the lithium-ion battery. From Examples 1-2 and 3-1 to 3-12, it can be seen that the lithium-ion battery within the scope of the present application that regulates the values ​​of P, T, and Y has a lower thickness expansion rate, a lower low-temperature voltage drop, a higher high-temperature cycle capacity retention rate, a higher hot box test pass rate, and a higher high-temperature floating cycle capacity retention rate, indicating that the lithium-ion battery has better safety performance, low-temperature discharge performance, high-temperature cycle performance, high-temperature storage performance, and high-temperature floating performance.

[0125] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method or article including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method or article.

[0126] The terms "one of", "one of", "a kind of" or other similar terms connected to the elements refer to any one of the listed elements. For example, "one of A or B" means only A or only B; as another example, "one of A, B, and C" means only A, only B, or only C. The terms "at least one of", "at least one of", "at least one of" or other similar terms connected to the elements refer to any combination of the listed elements. For example, "at least one of A or B" means only A, only B, A and B. As another example, "at least one of A, B, or C" means only A, only B, only C, only A and B, only A and C, only B and C, A, B, and C.

[0127] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.

[0128] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. An electrolyte, wherein The electrolyte comprises lithium difluorophosphate, a dinitrile compound and diethyl carbonate, wherein the mass percentage of the dinitrile compound is A%, the mass percentage of the diethyl carbonate is B%, 10≤A+B≤24, 0.8≤A≤3 based on the total mass of the electrolyte; The electrolyte also includes propyl propionate and a trinitrile compound; based on the total mass of the electrolyte, the mass percentage of the trinitrile compound is C%, 2.6≤A+C≤3.

4.

2. The electrolyte according to claim 1, wherein 12≤A+B≤20.

3. The electrolyte according to claim 1, wherein 15≤A+B≤20.

4. The electrolyte according to claim 1, wherein Based on the total mass of the electrolyte, the mass percentage of the lithium difluorophosphate is E%, and 0.05≤E≤2.

5.

5. The electrolyte according to claim 1, wherein The electrolyte satisfies at least one of the following characteristics: a) 1≤A≤2.4; b) 10≤B≤20.

6. The electrolyte according to any one of claims 1 to 5, wherein Based on the total mass of the electrolyte, the mass percentage of the propyl propionate is D%, 22≤D≤40.

7. The electrolyte according to claim 6, wherein 30≤D≤40。 8. The electrolyte according to any one of claims 1 to 5, wherein The dinitrile compounds include succinonitrile, glutaronitrile, adiponitrile, 1,5-dicyanopentane, 1,6-dicyanohexane, 1,7-dicyanoheptane, 1,8-dicyanooctane, 1,9-dicyanononane, tetramethylsuccinonitrile, 2-methylglutaronitrile, 2,4-dimethylglutaronitrile, 2,2,4,4-tetramethylglutaronitrile, 1,4-dicyanopentane, 2,6-dicyanoheptane, 2,7-dicyanooctane, 2,8-dicyanononane, 1,6-dicyanodecane, 1,2-dicyanobenzene, 1,3-dicyanobenzene, 1,4-dicyanobenzene, 3,5-dioxa-pimelonitrile, 1,4-bis(cyanoethoxy)butane, ethylene glycol di(2-cyanoethyl) ether, diethylene glycol di(2-cyanoethyl) ether, triethylene glycol di(2-cyanoethyl) ether, tetraethylene glycol di(2-cyanoethyl) ether, 1,3-bis(2-cyanoethoxy)propane, 1,4-bis(2-cyanoethoxy)butane, ethylene glycol di(4-cyanobutyl) ether, 1,4-dicyano-2-butene, 1,4-dicyano-2-methyl-2-butene, 1,4-dicyano-2-ethyl-2-butene, 1,4-dicyano-2,3-dimethyl-2-butene, 1,4-dicyano-2,3-diethyl-2-butene, 1,6-dicyano-3-hexene or 1,6-dicyano-2-methyl-5-methyl-3-hexene.

9. The electrolyte according to claim 8, wherein The dinitrile compound includes at least one of adiponitrile or ethylene glycol bis(2-cyanoethyl) ether.

10. An electrochemical device, wherein: The electrochemical device comprises the electrolyte according to any one of claims 1 to 9.

11. The electrochemical device according to claim 10, wherein: The electrochemical device further comprises an isolation membrane, the isolation membrane comprising a base membrane and a porous coating layer located on at least one surface of the base membrane; the isolation membrane satisfies at least one of the following features: x) on the surface of the porous coating layer, in a 30 μm×40 μm region, the ratio of the apparent concentration of oxygen element to the apparent concentration of aluminum element is P, 1≤P≤2.5; y) the average wall thickness between adjacent pores in the porous coating is T nm, 25≤T≤450; z) The compression rate of the base film when compressed at 70° C. and a pressure of 2.5 MPa for 40 minutes is Y%, and 25≤Y≤55.

12. An electronic device, wherein: The electronic device comprises the electrochemical device according to any one of claims 10 to 11.

Citation Information

Patent Citations

  • High-energy density lithium ion battery and electrolyte thereof

    CN108598488A

  • Electrolyte and lithium ion battery comprising same

    CN112072180A

  • Electrolyte for improving high-temperature stability and lithium ion battery

    CN117996179A

  • KR20240005577A